2017
DOI: 10.1021/acs.energyfuels.7b02421
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Compositional Changes along In Situ Combustion and Their Implications on Emulsion Stabilization via Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS)

Abstract: In situ combustion (ISC) is one of the highest potential enhanced oil recovery (EOR) processes for heavy oils. However, several operational issues, including the formation of highly stable emulsions, have limited its application. Disclosing the physicochemical proprieties of these emulsions, especially the chemical nature of the compounds involved in the stabilization process, has become relevant for the success of ISC projects. In the present work, the physicochemical changes at a laboratory-scale low-tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…When using oxygen as an oxidant, multinuclear systems react readily as more rings are fused because less π-sextets can be shared and more double bonds are formed within the structure, and thus, the addition of oxygen is favored . Therefore, it can be concluded that under the reaction conditions employed, a preferential oxidation of the polyaromatic species occurred, which agrees with a previous study . In this order of ideas, it was observed that at 180 °C with and without the catalyst, compounds C29–31 with DBE 5 were concentrated, which could be associated with mono-aromatic hydrocarbon species refractory to the oxidation process, without ruling out that the derivatives of steranes and naphthenic compounds are also part of this group of compounds.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…When using oxygen as an oxidant, multinuclear systems react readily as more rings are fused because less π-sextets can be shared and more double bonds are formed within the structure, and thus, the addition of oxygen is favored . Therefore, it can be concluded that under the reaction conditions employed, a preferential oxidation of the polyaromatic species occurred, which agrees with a previous study . In this order of ideas, it was observed that at 180 °C with and without the catalyst, compounds C29–31 with DBE 5 were concentrated, which could be associated with mono-aromatic hydrocarbon species refractory to the oxidation process, without ruling out that the derivatives of steranes and naphthenic compounds are also part of this group of compounds.…”
Section: Resultssupporting
confidence: 90%
“…When the reactions occur at 180 °C, the percentage of acids was almost the same for RU and CH (35 and 37%, respectively) and almost double for CA (61%). This acidity changes could be related to the formation of oxygen compounds due to LTO reactions as was found previously Figure also shows that the catalyst reduced the percentage of acids in the RU, but it increases in CH and CA.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations